Characterizing subpopulations of neoplastic cells in serous effusions - the role of immunocytochemistry - Queiroz, C.; Barral-Netto, M.; Bacchi, C. E. (Sci Printers & Publ Inc, 2001)
OBJECTIVE: To analyze the role of immunochemistry in serous effusions.STUDY DESIGN: We analyzed cell blocks of 18 pleural and 18 peritoneal effusions diagnosed as malignant (18), benign (14) and suspicious (4). They were immunostained by the avidin-biotin complex method with a panel of four monoclonal antibodies-CEA, Ber-EP4, LeuM1 (CD15) and r53-and for lectins (Ulex europaeus) UEA-1, ConA and ConBr. RESULTS: Seventeen of the 18 cases of adenocarcinoma were positive for CEA (95%), 12 (66.6%)for Bev-EP4, 11 (61 %)for CD15 nild 11 (62 %)for p53. Twelve of the 18 (66.6%) were positive for UEA-1, CEA, Ber-EP4 and CD15. UEA-1 did not react with mesothelial cells. p53 Gave a positive reaction in only one case, reactive mesothelial cells. ConA and ConBr reacted indiscriminately with benign and malignant cells; thus, it was not useful in distinguishing between these cells.CONCLUSION: In this context no antibody used alone is reliable for corroborating a diagnosis, but the selective use of a small panel of three markers (CEA, Ber-EP4 and LeuM1) can be very useful in solving diagnostic difficulties in the cytodiagnosis of serous effusions.
Keywords: cells; neoplasms; immunocytochemistry; serous effusions